Accelerated Molecular Dynamics Simulation for Helical Proteins Folding in Explicit Water - Duan, Lili; Guo, Xiaona; Cong, Yalong; Feng, Guoqiang; Li, Yuchen; Zhang, John Z. H. (Frontiers in Chemistry, 2019)
In this study, we have studied the folding process of eight helical proteins (2I9M, TC5B, 1WN8, 1V4Z, 1HO2, 1HLL, 2KFE, 1YYB) at room temperature using the explicit solvent model under AMBER14SB force field by the accelerated molecular dynamics (AMD) and traditional molecular dynamics at the same simulation time, respectively. We analyze and compare the two simulation results from several aspects, such as RMSD, native contacts, cluster analysis, folding snapshots, free energy landscape and the detail of the radius of gyration etc., which show these eight proteins are successfully fold into the corresponding native structures consistently using AMD simulation. In addition, the folding time occurs in the range of 40~180ns starting from their linear structures for the eight proteins. On the contrary, these stable folding structures are not found when the traditional MD simulation is used. In order to furtherly investigate the efficiency of AMD, another trajectory is again ran for three small proteins (2I9M, TC5B, 1WN8) with the same linear structure but different random seeds. Both AMD trajectories reach their corrected folding structures. Our study clearly shows the high efficiency and reliable simulation in the protein folding study using AMD method.